2014
DOI: 10.3109/00016357.2014.971868
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermocycling on roughness of nanofill, microfill and microhybrid composites

Abstract: The composition of material, including the type of organic matrix, could be more relevant to roughness maintenance over time than the general behavior of composites based on particles fillers. The maintenance of smooth surface in resin-based composite restorations is totally dependent of organic composition of the material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
4
20
0
3
Order By: Relevance
“…The variation of filler exposure after thermal cycling is probably due to matrix degradation, which causes the exposure of the filler particles within and thus, results in higher roughness values . Several investigations have focused on the effects of thermocycling on microhardness, roughness, and color of composite restorations . Dos Santos and colleagues reported that 3,000 thermal cycles increased roughness values for all resin‐based composites and there was a tendency for reduced surface roughness values after 10,000 thermal cycles.…”
Section: Discussionmentioning
confidence: 99%
“…The variation of filler exposure after thermal cycling is probably due to matrix degradation, which causes the exposure of the filler particles within and thus, results in higher roughness values . Several investigations have focused on the effects of thermocycling on microhardness, roughness, and color of composite restorations . Dos Santos and colleagues reported that 3,000 thermal cycles increased roughness values for all resin‐based composites and there was a tendency for reduced surface roughness values after 10,000 thermal cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Thermocycling is a popular method of artificial accelerated aging of ceramics because it reproduces the oral environment as an extrinsic factor [24][25][26]. The water aging method includes standardized thermal variations with baths ranging from 5 to 55 • C for several cycles.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these changes, mechanical stresses and crack formations occur [26]. In literature, bath temperature and a number of cycles have not been standardized, but a short dwell of 15-20 s represents the changes in temperature in the oral environment [27][28][29]. Longer exposure times are not well tolerated [30].…”
Section: Introductionmentioning
confidence: 99%